Social Support and The Risk of Aggressive Behavior among Adolescents in Cirebon City - Endah Sari Purbaningsih; Muadi Muadi; Sri Kamila (Riviera Publishing, 2024)
Aggressive behavior among adolescents, such as brawls, has become increasingly prevalent, particularly in school environments. This study investigates the relationship between social support and the risk of aggressive behavior among adolescents at SMK Muhammadiyah Cirebon City. Utilizing a descriptive correlation design with a cross-sectional approach, the study involved 152 students, with 60 respondents selected through proportional random sampling. Data collection utilized a reliable social support questionnaire and a risk of aggressive behavior questionnaire. The analysis revealed that 65.0% of respondents received moderate social support, while 61.7% were at risk of aggressive behavior. Notably, a significant and very strong negative correlation was found between social support and the risk of aggressive behavior (p = 0.000, ? = 0.05, r = -0.886). This indicates that higher levels of social support are associated with a substantially lower risk of aggressive behavior. The study recommends implementing counseling programs to enhance social support for students at risk of aggression.